(untitled) (International relations and international law Journal, 2016)
This article examines the views of international news sources on the internal structure of the modern Arab world, which is the whole geopolitical, cultural and religious space in North Africa and West Asia. Recent years in the Arab world has undergone several important event. Tide of revolution swept the Middle Eastern countries of Bahrain to Yemen, from Libya to Tunisia and Morocco. These events have become an important issue in international relations in the twentyfirst century , and the main themes of the international media. We can determine that this article is relevant as regards the views of the world’s media to the "Arab Spring". The subject of this article is the crucial role of the international media in delivering accurate information about the internal structure of the modern Arab world.